2018
DOI: 10.3168/jds.2018-15137
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the natural killer cell activity and anti-influenza effect of heat-treated Lactobacillus plantarum nF1-fortified yogurt in mice

Abstract: Influenza A virus (IAV) infection is a global public health concern. It causes respiratory diseases ranging from mild illness to fatal disease. Natural killer (NK) cells are an innate immune component that kill infected cells and secrete cytokines to modulate the adaptive immune system; they constitute the first-line defense and play important roles in controlling IAV infection. This study evaluated the effect of daily administration of heat-treated Lactobacillus plantarum nF1-fortified yogurt on immunity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…A large body of evidence has suggested that L. plantarum strengthens several aspects of the host defense mechanism against the infection by respiratory viruses, particularly seasonal and highly pathogenic influenza viruses. For example, oral administration of L. plantarum in mice significantly suppressed viral replication in the lungs and reduced airway inflammation, thereby increasing survival rates (33)(34)(35)(36)(37)(38)(39). The underlying immunological effects are known to be diverse, including stimulation of type I IFN production (37,39), enhancement of NK cell activity (36,39), promotion of T helper type 1 cell-mediated immune responses (33,34,39) and activation of IgA-dependent mucosal immunity in the small intestine and lung (34,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of evidence has suggested that L. plantarum strengthens several aspects of the host defense mechanism against the infection by respiratory viruses, particularly seasonal and highly pathogenic influenza viruses. For example, oral administration of L. plantarum in mice significantly suppressed viral replication in the lungs and reduced airway inflammation, thereby increasing survival rates (33)(34)(35)(36)(37)(38)(39). The underlying immunological effects are known to be diverse, including stimulation of type I IFN production (37,39), enhancement of NK cell activity (36,39), promotion of T helper type 1 cell-mediated immune responses (33,34,39) and activation of IgA-dependent mucosal immunity in the small intestine and lung (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, certain proinflammatory LAB strains are known to induce innate cytokine changes that can trigger early antiviral immune responses and may therefore be employed prophylactically (32,33). Notably, previous preclinical studies and randomized controlled trials have demonstrated that among probiotic LAB, Lactobacillus plantarum (L. plantarum) (33)(34)(35)(36)(37)(38)(39), Bif idobacterium longum (B. longum) (40,41) and Lactococcus lactis ssp. Lactis (L. lactis ssp.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple previous preclinical and clinical studies and reviews have provided data and suggested mechanistic insights explaining glycemic and other health benefits of yogurt and probiotics. These mechanisms involve all organs and systems from the brain to the gut and the immune system and are mediated by pathways related to pancreatic beta-cell preservation [60], hepatic glucose production [61], incretin hormones synthesis and secretion [62], peroxisome proliferator-activated receptors [63], fatty acid oxidation [64], endotoxin [65], innate immunity [66], and appetite suppression [67] among others. In addition to the benefits of yogurt, kefir could offer a unique antidiabetic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Potential probiotic strains of L. plantarum could be used in starter cultures or used as adjunct bacteria without adverse effects on product quality or sensory properties of fermented milk products (Dan et al, 2019). Many recent studies have reported that consuming L. plantarum-containing fermented milk exerts in vivo functionality to the host (Nasrabadi et al, 2011;Kim et al, 2018).…”
Section: Introductionmentioning
confidence: 99%